Economic complexity and bilateral trade flows in selected COMESA and East Asia countries - Abdikafi Hassan Abdi; Mohd Azlan Shah Zaidi; Zulkefly Abdul Karim (Technological and Economic Development of Economy, 2023)
A particular country’s productive knowledge and sophistication become a crucial determinant for the exported products in the increasingly integrated global trade. However, studies that emphasize the connection between economic complexity and trade flows are still sparse. This research aims to examine the role of economic complexity on bilateral trade flows of 27 countries in COMESA and East Asia using the gravity model from 1995 till 2019. Based on countries’ geographical regions and income levels, the empirical estimation of the study applied the Poisson pseudo maximum likelihood (PPML) estimator. The main results are robust to various model specifications and consistent with the expectations of the gravity model indicators. The study found strong empirical evidence that the expansion of economic sophistication and diversification enlarges trade flows of different exported goods. Explicitly, economic complexity increases the exports of machinery and transport equipment alongside manufactured products, while its effects on agricultural exports are negligible. Thus, this study proposes that the countries should engage in more sophisticated Research and Development (R&D), attract multinational companies, establish industrial policies, and improve their productivity by utilizing the existing production network. They should move to a more diversified production and trade structure to enhance their bilateral trade flows.